(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Majority of patients with bladder cancer present with superficial tumor, which is of three types: papillary carcinoma confined to the bladder epithelium, tumor invading but confined to the lamina propria, and carcinoma in situ (cis). Transurethral resection represents the effective management of superficial tumors but with high recurrence rate (75%) that can be minimized to 50% by using cytotoxic drug or immunotherapy. Objective:To compare two method lines of treatment in respect to long - term versus short - term therapy of Mitomycin C (MMC)Intravesical instillation after transurethral resection of superficial transitional carcinoma of urinary bladder to detect the duration of disease free interval, recurrence rate and adverse effects. Methods: A prospective, randomized, two parallel and compared lines of treatment study involved 50 patients who were evaluated after transurethral resection of superficial bladder cancer with median follow-up of 30 months. They were informed about the study and their approval to participate in the study was taken. Group A (25 patients) received intravesical MMC 30 mg weekly for 6 weeks, while group B (25 patients) continue to receive further 12 monthly instillations. Statistical analysis was performed by using Kaplan - Meier methods and chi square test. Results:After follow-up of 30 months, 28% of patients who received short course of intravesical MMC were disease free in comparison to those with long – term treatment in group B which shows significantly higher rate of disease free (56%). Regarding the adverse effects, no significant differences in incidence were noted between two groups. Conclusion:The data from the present study confirm both efficacy and safety of using intensive, prolong regimen of intravesical MMC instillation for superficial bladder cancer. Key words: Mitomycin C, superficial transitional carcinoma, and transurethral resection.